Pattern and Distribution of Refractive Error Types in North Indian Children: A Clinical Cross-Sectional Study. - Pandey, Ambrish Kumar; Tripathi, Himanshu; Singh, Dilip; Kumar, Rajesh (Journal of Neonatal Surgery, 2025)
eye care center. Methods: A clinical cross-sectional investigation, 183 children, ranging in age from 6 to 15, who had thorough eye exams were included. Using streak retinoscopy and an autorefractometer, we measured visual acuity and performed objective refraction. Refractive errors were categorized by severity: myopia, hypermetropia, hyperopic astigmatism, and mixed astigmatism. Using descriptive statistics, we looked at how refractive errors were distributed by gender and age. Results: Myopia was the predominant refractive error, impacting 87 children (47.54%), followed by myopic astigmatism in 70 children (38.25%). Hypermetropia and hyperopic astigmatism were few, representing 7.10% and 6.01% of instances, respectively, but mixed astigmatism occurred in 1.09% of children. The majority of participants were aged 11 to 14 years, with the highest prevalence observed in the 13 to 14-year age group. The gender distribution was almost balanced, with 90 boys (49.18%) and 93 girls (50.82%). Conclusion: The research reveals a prevalence of myopia and myopic astigmatism in North Indian children, signifying an increasing tendency of myopia in this demographic. Prompt refractive assessment and quick optical intervention are crucial to mitigate the incidence of preventable visual impairment in children...